Development of Cultural Tourism in Glodok China Region - Davi Ayu Andini; Liliana Dewi (CV ODIS, 2022)
Chinatown, Glodok became one of the cultural-based tourism where the place is very attached to Chinese Culture. Cultural Tourism is one tourism activity that presents cultural attraction distinguished from other special interests of tradition or advocacy. Glodok Chinatown significantly linked to Chinese culture and culinary tourism that is still diverse with Chinese foods, old buildings are maintained, and the surrounding community, whose majority ethnic group. This study was conducted in Chinatown, Glodok West Jakarta. Data collection by interview and observation. At the same time, the method of analysis used is descriptive qualitative analysis. The problem formulation focused on 1) How the community's efforts in preserving and developing a culture in Chinatown, Glodok 2. How do cultural tourism activities have an impact on tourism development in Chinatown? Glodok the results of this study show that cultural tourism Glodok Chinatown has an attraction to culture-based tourism.